2008
DOI: 10.1007/s11244-008-9080-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Porous α-Fe2O3 Nanorods as Catalyst Support and A Novel Method to Deposit Small Gold Colloids on Them

Abstract: Two novel methods, one for preparation of porous a-Fe 2 O 3 nanorod catalyst support and another for the deposition of gold (Au) particles on the catalyst support with high efficiency and high dispersion, were reported. In the former, FeO(OH) nanorods were first prepared by a mild hydrothermal synthesis using tetraethylammonium hydroxide (TEAOH) as the structure director. The FeO(OH) product was then converted to porous a-Fe 2 O 3 nanorods via calcination at 300°C. During this calcination, pores with a size di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Hematite (a-Fe 2 O 3 ) is the most active and stable iron oxide under ambient conditions, and is widely used as a catalyst, support or sensor. 17,24,28,31,[35][36][37][38][39][40][41][42] The shape and size of a-Fe 2 O 3 nanoparticles are also important for their chemical and physical properties. Gedanken and co-workers found that the catalytic activity can be improved by using a-Fe 2 O 3 nanorods with pores, of a size comparable to the size of very small Au nanoparticles (1-5 nm), so that these pores are suitable to accommodate or fix gold inside them.…”
Section: Introductionmentioning
confidence: 99%
“…Hematite (a-Fe 2 O 3 ) is the most active and stable iron oxide under ambient conditions, and is widely used as a catalyst, support or sensor. 17,24,28,31,[35][36][37][38][39][40][41][42] The shape and size of a-Fe 2 O 3 nanoparticles are also important for their chemical and physical properties. Gedanken and co-workers found that the catalytic activity can be improved by using a-Fe 2 O 3 nanorods with pores, of a size comparable to the size of very small Au nanoparticles (1-5 nm), so that these pores are suitable to accommodate or fix gold inside them.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that the shape and size of α-Fe 2 O 3 nanoparticles have a great impact on their chemical and physical properties such as, on magnetic 11,12 and catalytic properties. 13,14 The size-and shape-dependent properties of hematite nanoparticles have stimulated much effort towards the controlled synthesis of α-Fe 2 O 3 nanoparticles. So far, various methods including the sol-gel process, 6 thermal oxidation of iron metal, 9 the hydrothermal approach 4,15 and thermal decomposition 2,16 have been used to prepare α-Fe 2 O 3 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…116,154,155 In the latter case, gold colloids were immobilised on a-Fe 2 O 3 and TiO 2 , by reduction of HAuCl 4 with NaBH 4 in the presence of lysine as capping reagent and under sonication. The suspension had to be adjusted to a pH equal to or higher than the PZC of the supports to allow adsorption (see Table 2.1).…”
Section: Sonication-assisted Reductionmentioning
confidence: 99%